Culture or masculinity? Understanding gender-based violence in the UK. (1st February 2016) - Dustin, Moira
Abstract : Violence against women and girls from minority communities has been a focus for intervention in European countries for several decades. These initiatives have, however, tended to exist in isolation from strategies on violence against women and girls from majority groups. Taking the UK as a case study, this paper argues that when minorities are involved in gender-based violence, whether as victims or perpetrators, culture is problematised rather than masculinity in a way that is unhelpful in preventing these crimes.